2019
DOI: 10.3389/fimmu.2019.00602
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Radiochemotherapy Significantly Alters the Phenotype of Plasmacytoid Dendritic Cells and 6-Sulfo LacNAc+ Monocytes in Rectal Cancer

Abstract: Neoadjuvant radiochemotherapy (nRCT) can significantly influence the tumor immune architecture that plays a pivotal role in regulating tumor growth. Whereas, various studies have investigated the effect of nRCT on tumor-infiltrating T cells, little is known about its impact on the frequency and activation status of human dendritic cells (DCs). Plasmacytoid DCs (pDCs) essentially contribute to the regulation of innate and adaptive immunity and may profoundly influence tumor progression. Recent studies have reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 66 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Finally, the additional markers were integrated one-by-one until a six-plex panel was created, while making sure that the pattern of each marker did not change from uni- to multiplex. For all the TSA immunofluorescence stainings, tissue deparaffinization and hydration were performed as described before [ 50 ]. For antigen retrieval, all tissue sections underwent a microwave treatment in AR9 buffer (Akoya Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the additional markers were integrated one-by-one until a six-plex panel was created, while making sure that the pattern of each marker did not change from uni- to multiplex. For all the TSA immunofluorescence stainings, tissue deparaffinization and hydration were performed as described before [ 50 ]. For antigen retrieval, all tissue sections underwent a microwave treatment in AR9 buffer (Akoya Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…The influence of chemotherapy on the population of tumor-infiltrating pDCs is not well understood. Wagner et al disclosed that neoadjuvant radio-chemotherapy in rectal cancer resulted in significant increase of pDC frequencies in the tumor stroma, particularly in the population of INF-α + cells [71]. Previous studies investigating the role of pDCs in breast cancer showed that transforming growth factor-β (TGF-β) and tumor necrosis factor-α (TNF-α) abundant in the tumor microenvironment impaired production of INF-α in pDCs [72].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SseK1, SseK2, SseK3, and/or SteE may function at a late stage of infection, since these effectors were translocated through T3SS-2 or both T3SS-1 and T3SS-2 [ 32 , 33 , 35 ]. Several studies have reported that other effectors of T3SS-2 or of both T3SS-1 and T3SS-2—i.e., AvrA, GogB, SpvD, SseL, SspH1, and SteA—inhibit NF-κB activation [ 8 12 , 47 ]. Interestingly, as shown in Fig 2A , the level of NF-κB activity was low In HeLa cells infected with the S .…”
Section: Discussionmentioning
confidence: 99%